2023
DOI: 10.13057/biodiv/d240127
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and physical factors affecting the appearance of selected terrestrial birds in Khao Yai National Park using camera trapping

Abstract: Abstract. Kanka P, Sukmasuang R, Duengkae P, Siripattaranugul K. 2023. Abundance and physical factors affecting the appearance of selected terrestrial birds in Khao Yai National Park using camera trapping. Biodiversitas 24: 222 232. This study used results from camera traps set for Dhole (Cuon alpinus) and their prey during 2017-2020 in Khao Yai National Park to assess the species richness of ground-dwelling birds and identify abundance and also temporal appearance of the species in the area. We selected only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Interestingly, this study's results align with those of Chhetri et al (2021), who concluded that the most critical parameter affecting the occurrence of three Himalayan pheasant species was climate, followed by physical or topographic and biophysical factors respectively. The study also found that the type of forest influencing the occurrence of both species is the dry evergreen forest, which is consistent with research conducted on pheasants in the KYNP area (Kanka et al 2023). Chhetri et al (2018Chhetri et al ( , 2021 also noted that temperature is crucial in the Himalayas, and as a result, many species may experience changes in their range, expansion, or contraction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, this study's results align with those of Chhetri et al (2021), who concluded that the most critical parameter affecting the occurrence of three Himalayan pheasant species was climate, followed by physical or topographic and biophysical factors respectively. The study also found that the type of forest influencing the occurrence of both species is the dry evergreen forest, which is consistent with research conducted on pheasants in the KYNP area (Kanka et al 2023). Chhetri et al (2018Chhetri et al ( , 2021 also noted that temperature is crucial in the Himalayas, and as a result, many species may experience changes in their range, expansion, or contraction.…”
Section: Discussionsupporting
confidence: 88%
“…In the case of ground-dwelling bird species photographed in the study area, 10 such species were observed, including 2 pheasant species. This number is lower than the diversity of grounddwelling bird species recorded using camera traps in Khao Yai National Park (KYNP) and Huai Kha Khaeng Wildlife Sanctuary (HKKWS), as reported by Kanka et al (2023) and Charaspet et al (2021), respectively. Specifically, in KYNP, 36 ground-dwelling species, including 4 pheasant species, were recorded, while HKKWS documented 23 ground-dwelling species, including 5 pheasant species.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This approach has traditionally been used to gather information on various aspects of large terrestrial mammals such as occurrence (Salvatori et al 2023), abundance (Taylor et al 2022, Santini et al 2022) and behaviour patterns (Li et al 2020, Gracanin andMikac 2022), but nowadays it is used increasingly also for birds (Caravaggi et al 2017). It is especially useful in the study of ground dwelling birds, where game cameras have been recently used to describe, for example, activity patterns (Nykänen et al 2021), foraging (Sperry et al 2021), habitat use (Firth et al 2020, Puffer et al 2021, abundance (Kanka et al 2023) and predation pressure (Laux et al 2022).…”
Section: Introductionmentioning
confidence: 99%